Associations of body image with depressive symptoms and PTG among breast cancer patients: The mediating role of social support - Li, Mengyao (Frontiers in Psychology, 2022)
Background Cancer diagnosis and treatment usually trigger positive and negative psychological health outcomes. Social support is a coping resource of psychological health outcomes. However, little research is available on the relationships between social support, body image and overall psychological health outcomes in breast cancer (BC) patients. This study aimed to estimate the prevalence of depressive symptoms and post-traumatic growth (PTG), and examine the mediating roles of social support between body image and depressive symptoms and PTG among BC patients, respectively. Methods A cross-sectional study was conducted in Northeast of China from December 2015 to August 2017. All the participants were diagnosed with BC and underwent surgery. This study was conducted with 405 BC patients from the First Affiliated Hospital of China Medical University. Participants completed Center for Epidemiologic Studies Depression scale, Post Traumatic Growth Inventory, Body Image Scale, and Perceived Social Support Scale. The associations of social support, body image with depressive symptoms and PTG were examined by hierarchical linear regression analysis. Asymptotic and resampling strategies were used to explore the mediating role of social support. Results The prevalence of depressive symptoms was 88.1%, and 67.2% of the patients had moderate‐high PTG, 52.84% of the patients had body concerns, and 264(65.19%) patients had high-level social support. Body image was positively associated with depressive symptoms (β =0.445, P < 0.001), social support were negatively associated with depressive symptoms (β =-0.219, P < 0.001). Body image was negatively associated with PTG (β =-0.095, P=0.023), whereas social support was positively associated with PTG (β =0.533, P < 0.001). Social support significantly mediated the associations between body image and depressive symptoms (effect size = 0.057) and PTG (effect size = -0.304), respectively. Conclusions Social support played mediating roles in the relationships between body image and depressive symptoms and PTG. The interventions based on social support and body image should be included in psychological health prevention.